2013
DOI: 10.3389/fpsyg.2013.00306
|View full text |Cite
|
Sign up to set email alerts
|

Pathological gamblers are more vulnerable to the illusion of control in a standard associative learning task

Abstract: An illusion of control is said to occur when a person believes that he or she controls an outcome that is uncontrollable. Pathological gambling has often been related to an illusion of control, but the assessment of the illusion has generally used introspective methods in domain-specific (i.e., gambling) situations. The illusion of control of pathological gamblers, however, could be a more general problem, affecting other aspects of their daily life. Thus, we tested them using a standard associative learning t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
43
0
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 54 publications
(48 citation statements)
references
References 78 publications
2
43
0
3
Order By: Relevance
“…For example, money is a clear external reinforcer that results in a conditioned instrumental response; namely, gambling. In the problem gambler the response to the conditioned stimulus is different to that seen in recreational gamblers [5]. Nevertheless, we suggest that this is best understood using a common underlying psychological mechanism, but that the difference between the problem and the recreational gambler may be one of a parameter shift governing the associative strength between the behaviour and its reward, or the valuation of the reward.…”
Section: Kardefelt-winther Et Almentioning
confidence: 70%
“…For example, money is a clear external reinforcer that results in a conditioned instrumental response; namely, gambling. In the problem gambler the response to the conditioned stimulus is different to that seen in recreational gamblers [5]. Nevertheless, we suggest that this is best understood using a common underlying psychological mechanism, but that the difference between the problem and the recreational gambler may be one of a parameter shift governing the associative strength between the behaviour and its reward, or the valuation of the reward.…”
Section: Kardefelt-winther Et Almentioning
confidence: 70%
“…Orgaz et al (2013) previously found results that indicated a stronger illusion of control among individuals with GD. In this regard, Cowley and colleagues (2015) noted that people that felt their illusion of control was threatened by a bet lost were more likely to construct their retrospective evaluation of their gambling activity by giving a disproportionate importance to those bets in which they won, whereas participants with low illusory control beliefs (or those who have won) were more likely to re-tell their own gambling story considering the final outcome as baseline for the evaluation.…”
Section: Control Perception In Gamblingmentioning
confidence: 87%
“…Participants first completed the questionnaires (order: Gambling Questions, PGSI, GRCS, Barratt Impulsiveness Scale, Beck Depression Inventory, PANAS (state), SSS-V) and a computerised contingency judgement task that probed the illusion of control, a cognitive bias in gambling [32]. These were completed in laboratory settings in the School of Psychology at The University of Nottingham.…”
Section: Methodsmentioning
confidence: 99%